Provisioning of Applications with Network Requirements on Cloud-Edge Continuum - Albuquerque, Paulo Roberto; Koslovski, Guilerme Piêgas (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2024: Anais da XXIV Escola Regional de Alto Desempenho da Região Sul, 2024)
New challenges regarding the users mobility and network latency are observed in the provisioning of distributed applications atop Cloud Continuum scenarios. This requires a analysis from the perspectives of users and service providers. This article proposes a way to create provisioning policies based on user mobility and mass demands, while also analyzing the individual Services that compose some Application, analyzing their needs and restrictions.